Risks of the Tourism Industry in Ukraine - SOFIICHUK, Kateryna (Journal of Environmental Management and Tourism; Vol 9 No 2 (2018): JEMT Volume IX Issue 2(26) Spring 2018, 2018)
Tourism industry provides economic growth in all over the world. In the same time Ukrainian tourism industry going through hard times. The purpose of the study is to identify and assess the existing risks of the tourism industry in Ukraine, excluding the East of Ukraine, and explore the preconditions for avoiding or reducing these risks. Being that it is necessary to strengthen the image of Ukraine as a reliable state for travel in the foreign tourist’s eyes. The object of a study is the process of managing the risks of the tourism industry at the state level. The main hypothesis of the study is that the growth of the contribution of tourism to the country's GDP depends on the risks of the tourist enterprises and the level of the tourist’s risks in Ukraine. The theoretical base of risks in tourism and the dynamics of Ukrainian tourist arrivals and amount of tourist enterprises were considered in the study. The model of risk management in tourism is developed in the paper. The methodological basis were the following scientific methods: analysis and synthesis (for identification and evaluating types of touristic hazards in Ukraine), theoretical search and abstract-logical (for analyzing a risk management approaches), expert method (for identification and assessing an influence of tourism risks); graph method (to describe arrivals number and to forecast amount of enterprises in Ukraine); the method of least squares was used for the forecasting of the number of tourist enterprises in Ukraine; the principal component analysis method for grouping risks in Ukraine. The analysis of the future risks of the tourism industry of Ukraine was conducted. According to the results of the investigation, the recommendations about measures which should be taken by the state to manage and prevent risks were proposed.